2016
DOI: 10.1016/j.psyneuen.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hair cortisol concentration, income, income dynamics and status incongruity in healthy middle-aged women

Abstract: HighlightsWe examined associations of income and income dynamics with hair cortisol.We found a gradient negative relationship between hair cortisol and income.A negative change in income was related to higher hair cortisol.Social incongruity (a mismatch in education and income) affected hair cortisol.Our finding supports a relative income effect, but not an absolute income effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…19 Some studies have also reported a negative association between hair cortisol and socioeconomic status in children [20][21][22] and in adults. 23 However, null associations between socioeconomic status and hair cortisol have also been reported. 24,25…”
Section: Overcoming Methodological Challenges In Measuring Hpa Functimentioning
confidence: 99%
“…19 Some studies have also reported a negative association between hair cortisol and socioeconomic status in children [20][21][22] and in adults. 23 However, null associations between socioeconomic status and hair cortisol have also been reported. 24,25…”
Section: Overcoming Methodological Challenges In Measuring Hpa Functimentioning
confidence: 99%
“…Finally, the negative association between CA3-DG and hair cortisol in children should be interpreted with caution until further variables beyond hair color can be ruled out as potential confounds. For instance, there is some evidence that hair washing, or repeated exposure to water (e.g., regular swimming) can leach cortisol out of primate 106 and human hair 107 , although human evidence is mixed and suggests that proximal segments of hair are not affected 107,108 . Importantly, a concurrent study similarly finding a negative CA3-DG -hair cortisol association, has successfully ruled out the modifying effect of hair washing 93 .…”
Section: Regression Pathsmentioning
confidence: 99%
“…In adults, one study reported that lower income was associated with higher HCC (Serwinski et al, 2016), but others have not found differences in adult HCC by income (Chen et al, 2013; Wosu et al, 2015) or education (Serwinski et al, 2016; Wosu et al, 2015). In children, some studies have reported that lower parental education (Rippe et al, 2016; Vaghri et al, 2013; Vliegenthart et al, 2016) and lower family income (Rippe et al, 2016) are associated with higher HCC, whereas others have not found associations between child HCC and parental income (Vaghri et al, 2013) or parental education (Groeneveld et al, 2013; Karlen et al, 2013; Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%